2004
DOI: 10.1103/physrevlett.93.106602
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Resonance State Probed by Spin-Polarized Tunneling in EpitaxialFe/MgO/FeTunnel Junctions

Abstract: The direct impact of the electronic structure on spin-polarized transport has been experimentally proven in high-quality Fe/MgO/Fe epitaxial magnetic tunnel junctions, with an extremely flat bottom Fe/MgO interface. The voltage variation of the conductance points out the signature of an interfacial resonance state located in the minority band of Fe(001). When coupled to a metallic bulk state, this spin-polarized interfacial state enhances the band matching at the interface and therefore increases strongly the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
111
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 20 publications
9
111
2
Order By: Relevance
“…4(f), three peaks are observed: Two symmetric ones are located at ±0.037 V attributed to magnon excitations [18]; the stronger one located only at −0.14 V reveals the asymmetry of the interfacial electronic structure. It has been previously attributed to the interfacial resonance state surviving in MTJ stacks with a high-quality bottom interface [31]. Previous studies have shown that it can be tuned by interface quality [21] or chemical doping [18].…”
Section: B Transport Measurementsmentioning
confidence: 99%
“…4(f), three peaks are observed: Two symmetric ones are located at ±0.037 V attributed to magnon excitations [18]; the stronger one located only at −0.14 V reveals the asymmetry of the interfacial electronic structure. It has been previously attributed to the interfacial resonance state surviving in MTJ stacks with a high-quality bottom interface [31]. Previous studies have shown that it can be tuned by interface quality [21] or chemical doping [18].…”
Section: B Transport Measurementsmentioning
confidence: 99%
“…7 Moreover, an interfacial resonance state located in the minority band of Fe ͑001͒, which has been probed by spin-polarized tunneling in epitaxial Fe/ MgO / Fe MTJs, causes the TMR to change sign from positive to negative above a critical voltage. 8 Here we report the observation of a high inverted magnetoresistance when the free layer in MgO-based MTJs switches at zero bias. A switch in the sign of the resistance change near zero applied field occurs as a function of the thickness of the pinned CoFeB layer next to the MgO barrier in an MTJ stack with a synthetic antiferromagnet.…”
mentioning
confidence: 97%
“…Inversions of TMR with varying bias voltage have already been reported for epitaxial spinvalves [12,13,14]. They most often occur due to the voltage-induced opening/closing of conduction channels associated with spin-polarized electronic bands or surface states close to the Fermi level.…”
mentioning
confidence: 98%
“…Assuming implicitly that Ni was (111)-oriented, the authors related the negative TMR to the theoretical prediction made by Karpan et al [6,7] of a negative tunneling spin polarization at the K point of the GPFE Brillouin zone. However, the voltage bias dependence of the TMR, which is critically important to understand the interfacial effects [12,13,14], has not been studied. Such bias dependence investigation is of primary importance in view of the recent first principle non-equilibrium transport calculations, which predict a non-trivial dependence of the spin polarization with varying applied voltage at Gr|Co(111) and Gr|Ni(111) interfaces [15].…”
mentioning
confidence: 99%